Equilibrium Implications of Delegated Asset Management under Benchmarking - Leippold, Markus; Rohner, Philippe (Review of Finance, 2012)
Abstract Despite the enormous growth of the asset management industry during the past decades, little is known about the asset pricing implications of investment intermediaries. Standard models of investment theory neither address the distinction between individual and institutional investors nor the potential implications of direct investing and delegated investing. In a model with endogenous delegation, the authors find that delegation leads to a more informative price system and lower equity premia. In the presence of relative return objectives, stocks exhibiting high correlations with the benchmark have significantly lower returns than stocks with low correlations. The authors' empirical results support the model's predictions.